Are Children on Family Farm Child Labours? - Mathema, Kanhaiya B. (Socio-Economic Development Panorama, 2008)
In order to get children involved in farm or any other labour, it is very important to understand the perceptions of their parents. Meanwhile, consideration should be given to the length of their involvement in such works since it restricts children from their schooling heavily drawing upon their future. Such work impairs the development and well-being of children. This article tries to expose the perceptions of parents about their children working in family farms. In addition, it touches upon the prevalence of child labour in different parts of the world. Socio-Economic Development Panorama, Vol. 1, No. 2(2007) pp. 63-70